Highly luminescent dual-phase CsPbBr3/Cs4PbBr6 microcrystals for a wide color gamut for backlight displays. Issue 47 (28th November 2022) - Naresh, V.; Jang, Taehyung; Pang, Yoonsoo; Lee, Nohyun
Abstract : Ultrasonication-assisted, ligand-free synthesis of CsPbBr3 /Cs4 PbBr6 dual-phase MCs exhibit diverse morphologies, confirming that CsPbBr3 NCs are the photoluminescent sites with PLQY of 82.7%. Abstract : Cesium lead bromide perovskite nanocrystals (NCs) embedded in Cs4 PbBr6 or CsPb2 Br5 matrices forming core/shell structures are promising luminescent materials that exhibit remarkable photoluminescence properties meeting the need in a wide range of applications while overcoming stability challenges. Here, we report the large-scale, ligand-free synthesis of dual-phase Cs4 PbBr6 /CsPbBr3 microcrystals (MCs) using ultrasonication at room temperature, exhibiting a high photoluminescence quantum yield (PLQY) of 82.7% and good stability. High-resolution transmission electron microscopy and X-ray photoelectron characterization confirm that CsPbBr3 NCs are embedded in the Cs4 PbBr6 matrix-forming CsPbBr3 /Cs4 PbBr6 dual-phase structure. The evolution of the luminescence properties with temperature suggests that the strong green emission results from direct exciton recombination in the isolated [PbBr6 ] 4− octahedra, which possess a large exciton binding energy of 283.6 meV. As revealed from their emission intensities, the dual-phase CsPbBr3 /Cs4 PbBr6 MCs demonstrate excellent stability against ultraviolet irradiation (76%), good moisture resistance (42.7%), and good thermal tolerance (51%). It is understood that such excellent PLQY and stability are due to the surface passivation of the CsPbBr3 NCs attributed to the large bandgap as well as the isolated [PbBr6 ] 4− octahedra separated by Cs + ions in the Cs4 PbBr6 crystal lattice. Finally, the suitability of the green-emitting CsPbBr3 /Cs4 PbBr6 material for achieving white-light emission and a wide color gamut is evaluated by constructing a prototype white light-emitting diode (w-LED) using CsPbBr3 /Cs4 PbBr6 and red-emitting K2 SiF6 :Mn 4+ materials taken in different weight ratios and combined with a blue light-emitting InGaN LED chip ( λ = 455 nm). The constructed w-LED device exhibits the color coordinates (0.3315, 0.3289), an efficacy of 68 lm W −1, a color rendering index of 87%, a color temperature of 5564 K, and a wide color gamut of ∼118.78% (NTSC) and ∼88.69% (Rec. 2020) with RGB color filters in the CIE 1931 color space. Therefore, based on our present findings, we strongly believe that the dual-phase CsPbBr3 /Cs4 PbBr6 material is a promising green-emitting phosphor for use in w-LEDs as the backlight of display systems.